PENERAPAN ASAS PRADUGA TAK BERSALAH KAITANNYA DENGAN UNDANG-UNDANG NOMOR 40 TAHUN 1999 TENTANG MEDIA PERS - Sabir Ibrahim (Journal of Law ( Jurnal Ilmu Hukum ), 2014)
ABSTRACT In today's digital age, every day the public is given a wide variety of news information, either by means of electronic media, in print, or online. The types of information that the public absorb are various. Some choose the news content of education, health, lifestyle, celebrities, politics, to law and criminal. Regardless the public's need to absorb latest news information presented by media, there is something overlooked, namely the balance of news. In fact, the balance of news determines the quality and sharpness of the information presented to the public. But the fact is, there are still some media that ignore resource balance in the news production process as set out in the code of ethics of journalists in Indonesia. As a result, the product of information presented is less balanced. In the realm of law, the function of media as a means of social control has been set out in Article 3 paragraph (1) of Law No. 40 of 1999 on Press. In Article 6 (a), this Law defines the role of national press to meet the public's right to know. Elucidation of the article states that the fulfillment of public's right to know will encourage the establishment of truth and justice. Both of the foregoing articles lead to conclusion that the supervision function by the media cannot be separated from its function as a medium of information and its role to meet the public's right to know. Only, it is only by enlightened and conscious community, the power is supervised. On the other hand, the optimal function of the media in enlightening the public thought as well as a means of social control require freedom. Press freedom in certain level and journalists freedom in carrying out their professional using journalism rules will become one of the pillars of the growth of Indonesian democracy.